2021
DOI: 10.3390/ijms22031469
|View full text |Cite
|
Sign up to set email alerts
|

Priming with a Seaweed Extract Strongly Improves Drought Tolerance in Arabidopsis

Abstract: Drought represents a major threat to plants in natural ecosystems and agricultural settings. The biostimulant Super Fifty (SF), produced from the brown alga Ascophyllum nodosum, enables ecologically friendly stress mitigation. We investigated the physiological and whole-genome transcriptome responses of Arabidopsis thaliana to drought stress after a treatment with SF. SF strongly decreased drought-induced damage. Accumulation of reactive oxygen species (ROS), which typically stifle plant growth during drought,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 108 publications
4
43
0
Order By: Relevance
“…Priming and foliar application with SuperFifty led to a better tolerance against drought stress in Arabidopsis thaliana, with primed plants showing better development than control plants. Moreover, electrolyte leakage was observed to decrease in treated plants, and the reduction in relative water content (RWC) and ROS accumulation due to drought were shown to be diminished [137]. More interestingly, plants primed with this SWE displayed a substantial amount of differently expressed genes, suppressing those with negative effects such as ROS accumulation and upregulating those with positive effects such as ROS scavengers.…”
Section: Ascophyllum Nodosummentioning
confidence: 93%
See 2 more Smart Citations
“…Priming and foliar application with SuperFifty led to a better tolerance against drought stress in Arabidopsis thaliana, with primed plants showing better development than control plants. Moreover, electrolyte leakage was observed to decrease in treated plants, and the reduction in relative water content (RWC) and ROS accumulation due to drought were shown to be diminished [137]. More interestingly, plants primed with this SWE displayed a substantial amount of differently expressed genes, suppressing those with negative effects such as ROS accumulation and upregulating those with positive effects such as ROS scavengers.…”
Section: Ascophyllum Nodosummentioning
confidence: 93%
“…It has been suggested that non-growth hormone components in seaweed, such as polysaccharides, may be responsible for growth enhancing effects induced by SWE [132,133]. Polysaccharides are major components of brown seaweeds [134], and recent studies show that a particular commercial Ascophyllum nodosum (Super Fifty) extract high in polysaccharides modulates a range of processes at the transcriptomic, metabolic and lipid levels [135][136][137]. The authors demonstrate that these changes involve multiple pathways and culminate in significant changes at the phenotypic level, including: tolerance to oxidative stress and abiotic stresses; reductions in Reactive Oxygen Species (ROS); reductions in electrolyte leakage and increases in plant growth.…”
Section: Seaweed Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreases in glucose, fructose, and fiber levels resulted in higher total recoverable sugar (TRS). Other studies have also reported a strong influence of polysaccharides that are abundant in various seaweed extracts, including those from A. nodosum , on vegetative parameters ( Craigie, 2010 ; Omidbakhshfard et al, 2020 ; Baltazar et al, 2021 ; Rasul et al, 2021 ). These non-growth hormone compounds modulate metabolic, lipid, and transcription pathways to promote phenotypic changes in plants that facilitate growth, such as improved resistance to stress, reduced ROS levels, and decreased electrolyte loss due to cell damage ( Craigie, 2010 ; Omidbakhshfard et al, 2020 ; Baltazar et al, 2021 ; Rasul et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have also reported a strong influence of polysaccharides that are abundant in various seaweed extracts, including those from A. nodosum , on vegetative parameters ( Craigie, 2010 ; Omidbakhshfard et al, 2020 ; Baltazar et al, 2021 ; Rasul et al, 2021 ). These non-growth hormone compounds modulate metabolic, lipid, and transcription pathways to promote phenotypic changes in plants that facilitate growth, such as improved resistance to stress, reduced ROS levels, and decreased electrolyte loss due to cell damage ( Craigie, 2010 ; Omidbakhshfard et al, 2020 ; Baltazar et al, 2021 ; Rasul et al, 2021 ). These phytotonic effects of SWE arise from the complex composition of metabolites, which are rich in macro- and micronutrients, carbohydrates, amino acids, and plant hormones, such as auxins and cytokinin ( De Abreu et al, 2008 ; Tan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%